Pameran Alat Peraga Sederhana Pembelajaran Fisika di SMA Negeri 3 Manokwari - Sri Wahyu Widyaningsih; Sri Rosepda Sebayang; Irfan Yusuf; Iriwi L.S. Sinon; Mujasam; Kaleb Amaghi Yenusi; Alberto Y.T Allo; Rismawati (CV. Multi Kreasi Media, 2023)
The purpuses of this activity are as follows: 1) socialization of Physics Education Study Program FKIP UNIPA, 2) Sharing knowledge in understanding physics concepts through visual aids. The socialization and community service activities at Manokwari 3 Public High School carried out by the Physics Education Department, FKIP UNIPA, went smoothly according to the schedule of events and the responses from the school, teachers and students were very kind by appreciating and thanking the presence of the team of lecturers and students of the Department of Physics Education who came to SMA Negeri 3 Manokwari and also provided props to be used in teaching physics at school.